A full-stage parallel architecture of three-dimensional discontinuous deformation analysis using OpenMP. (February 2020) - Peng, Xinyan; Chen, Guangqi; Yu, Pengcheng; Zhang, Yingbin; Zhang, Hong; Guo, Longxiao
Abstract: It can be computationally expensive to conduct large-scale engineering computation using three-dimensional discontinuous deformation analysis (3-D DDA). Improving the efficiency of 3-D DDA is thus imperative, and an available approach is to incorporate parallelism technique into 3-D DDA. In this paper, a full-stage parallelization of 3-D DDA is proposed, in which all the main subroutines that have the potential to be executed in parallel are implemented with parallelization using OpenMP. The correctness of the parallel 3-D DDA is examined by a block sliding example, showing good convergence between simulation results and analytical solutions. The computation efficiency is subsequently investigated through a set of masonry structures, and the parallel 3-D DDA exhibits good efficiency performance according to the comparison results. Afterwards, the application of the parallel 3-D DDA to large-scale colliding problem is carried out, demonstrating around 5 times enhanced efficiency with 6 threads used. Conclusively, the parallel 3-D DDA provides a more efficient approach to analyze large-scale problems than the serial conventional computation.